Activation of brain‐derived neurotrophic factor signaling in the basal forebrain reverses acute sleep deprivation‐induced fear memory impairments. Issue 4 (10th March 2020) - Ma, Tao; Zhang, Hao; Xu, Zhi‐Peng; Lu, Yan; Fu, Qiang; Wang, Wei; Li, Guan‐Hua; Wang, Ying‐Ying; Yang, Yi‐Tian; Mi, Wei‐Dong
Abstract: Introduction: The mechanisms underlying sleep deprivation‐induced memory impairments and relevant compensatory signaling pathways remain elusive. We tested the hypothesis that increased brain‐derived neurotrophic factor (BDNF) expression in the basal forebrain following acute sleep deprivation was a compensatory mechanism to maintain fear memory performance. Methods: Adult male Wistar rats were deprived of 6‐hr total sleep from the beginning of the light cycle. The effects of sleep deprivation on BDNF protein expression and activation of downstream tropomyosin receptor kinase B (TrkB)/phospholipase C‐γ1 (PLCγ1) signaling in the basal forebrain and fear memory consolidation were examined. BDNF or selective downstream TrkB receptor antagonist ANA‐12 was further injected into the basal forebrain bilaterally to observe the changes in fear memory consolidation in response to modulation of the BDNF/TrkB signaling. Results: Six hours of sleep deprivation‐induced both short‐ and long‐term fear memory impairments. Increased BDNF protein expression and TrkB and PLCγ1 phosphorylation in the basal forebrain were observed after sleep deprivation. Microinjection of BDNF into the basal forebrain partly reversed fear memory deficits caused by sleep deprivation, which were accompanied by increased BDNF protein levels and TrkB/PLCγ1 activation. After ANA‐12 microinjection, sleep deprivation‐induced activation of the BDNF/TrkB pathway was inhibited and impairments of fear memory consolidation were further aggravated. Conclusions: Acute sleep deprivation induces compensatory increase of BDNF expression in the basal forebrain. Microinjection of BDNF into the basal forebrain mitigates the fear memory impairments caused by sleep deprivation by activating TrkB/PLCγ1 signaling. Abstract : We found that acute sleep deprivation could increase BDNF protein expression and downstream TrkB/PLCγ1 activation robustly in the basal forebrain area. Microinjection of BDNF into basal forebrain could further activate TrkB/PLCγ1 signaling and reverse the decline in fear memory consolidation. Moreover, microinjection of TrkB receptor antagonist ANA‐12 could aggravate sleep deprivation‐induced memory impairments.